Root exudate glycine synergistically promotes phytoremediation of petroleum-contaminated soil - He, Mengfan; Li, Zhongbao; Mei, Ping (Frontiers in Environmental Science, 2022)
The exploitation of petroleum, the production and use of petroleum products causes pollution that is harmful to the ecology and environment. At present, petroleum hydrocarbon pollution has become a universal concern in the world. As one of the bioremediation methods, plant root exudate repair has the effect of eliminating toxic substances in the environment. To explore the role of root exudates glycine in phytoremediation of petroleum-contaminated soil, seed germination and pot experiments were carried out to study the effects of glycine on the degradation of petroleum hydrocarbons in different plants and soil types. The results showed that when the concentration of petroleum pollutants was constant, the order of seed germination rate of the eight plants was ryegrass > sudan grass > white clover > tall fescue > alfalfa > pennisetum > canine root > maize grass.1000 mg·L-1 of glycine could effectively promote plant biomass and the petroleum hydrocarbons degradation rate. The degradation effect was ryegrass + glycine > ryegrass > sudan grass + glycine > sudan grass > white clover + glycine > white clover. The degradation rate of ryegrass + glycine in 18000 mg·kg-1 petroleum-contaminated soil reached 55.7%. All plants had the highest biomass and plant height in loamy soil, while the highest degradation rate of petroleum hydrocarbons was observed in sandy soil, ranging from 50.36% to 59.36%. Among them, ryegrass combined with 1000 mg·L-1 of glycine reached the highest petroleum hydrocarbons degradation rate of 59.36% in sandy soil. Ryegrass, sudan grass and white clover had the potential to remediate petroleum-contaminated soils. In the three types of soil, ryegrass had a strong remediation efficiency, and the degradation effect to petroleum hydrocarbons was more significant after the addition of glycine. Therefore, ryegrass can be planted with glycine as a priority for remediation in oil field areas contaminated by petroleum hydrocarbons.